A SEARCH FOR CULTURAL IDENTITY IN THE SELECTED NOVELS OF AMITAV GHOSH - Wanjarri, Smeetaa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study delves into the theme of cultural identity in the selected novels of Amitav Ghosh, one of India’s most celebrated contemporary writers. His works are renowned for their rich exploration of cultural dislocation, historical memory, migration, and hybridity. This paper analyzes key texts, including The Shadow Lines, The Glass Palace, and The Hungry Tide, to uncover how Ghosh portrays the struggles and resilience of individuals in their quest for cultural belonging amidst the complexities of post-colonial, globalized landscapes. Using an interdisciplinary approach that combines post-colonial theory, cultural studies, and literary analysis, the study highlights Ghosh’s unique narrative techniques, his interweaving of history with fiction, and his portrayal of multicultural identities. The research aims to offer insights into how literature becomes a powerful medium for understanding the dynamics of identity, memory, and displacement in a globalized world.